2020
DOI: 10.1002/jsfa.10575
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between chlorophyll content of vine leaves, predawn leaf water potential at veraison, and chemical and sensory attributes of wine

Abstract: Background: Water deficit and iron deficiency (iron chlorosis) are common environmental stresses that affect grapevine production in the Mediterranean area. Studies on the impact of both stresses, when they act simultaneously, are rare. The main objective of this investigation was to evaluate the combined effects of the incidence of iron chlorosis and the vine water status on quality of Tempranillo wine. For this, 20 non-irrigated vineyard subzones (10 m × 10 m each), from non-affected to moderately affected b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
(82 reference statements)
0
0
0
Order By: Relevance
“…The values of osmotically active solutes in grapevines leaves were similar to those that have been documented by other authors [50]. Many studies have reported that drought stress leads to a general depletion of soluble sugars and starch in leaves [57,58] that results in the inhibition of photosynthesis, where stomata close and the internal CO 2 concentration decreases [22,59,60]. Nevertheless, experiments by other authors have reported that soluble sugars accumulate in leaves during drought stress [61].…”
Section: Discussionsupporting
confidence: 85%
“…The values of osmotically active solutes in grapevines leaves were similar to those that have been documented by other authors [50]. Many studies have reported that drought stress leads to a general depletion of soluble sugars and starch in leaves [57,58] that results in the inhibition of photosynthesis, where stomata close and the internal CO 2 concentration decreases [22,59,60]. Nevertheless, experiments by other authors have reported that soluble sugars accumulate in leaves during drought stress [61].…”
Section: Discussionsupporting
confidence: 85%
“…An article discusses how the levels of chlorophyll in the leaves and the amount of water in the leaves before sunrise, measured during the grapes' ripening stage, affect the wine's chemical and sensory properties. The presence of iron stress lowers the pH of the wine and improves sensory qualities like tone, intensity, and flavor, with a greater impact than the water levels [26].…”
Section: Wine Consumptionmentioning
confidence: 99%